Did the cooperative start life as a joint-stock company? Business law and cooperatives in Spain, 1869 - 1931 - Timothy W. Guinnane; Susana Martínez-Rodríguez (Yale University, Economic Growth Center, 2010)
Studies of Spanish cooperatives date their spread from the Law on Agrarian Syndicates of 1906. But the first legislative appearance of cooperatives is an 1869 measure that permitted general incorporation for lending companies. The 1931 general law on cooperatives, which was the first act permitting the formation of cooperatives in any activity, reflects the gradual disappearance of the cooperative's business characteristics. In this paper we trace the Spanish cooperative's legal roots in business law and its connections to broader questions of the freedom of association, the formation of joint-stock enterprises, and the liability of investors in business and cooperative entities. Our account underscores the similarities of the organizational problems approach by cooperatives and business firms, while at the same time respecting the distinctive purposes cooperatives served.
Keywords: N43; N23; K20; 330; cooperative; general incorporation; business enterprise; freedom of association; freedom of contract